Mapping the Use of Digital Game-Based Learning in Music Education: A Scoping Review - Rizky Fauzy Ananda; Rita Milyartini; Yudi Sukmayadi (Jurnal Pendidikan Indonesia, 2025)
Music education supports creative expression, emotional development, and cognitive growth. During the last several years, digital game-based learning (DGBL) has been used to maintain student engagement, but its presence in music education varies considerably. Some teachers experiment with small-scale game tools, while others adapt existing commercial games for classroom use. This study maps how digital games were used in music education from 2020 to 2025, a period shaped by the shift to remote and hybrid learning after COVID-19, when many educators had to reconsider how students could practice musical skills without face-to-face instruction. A scoping review was conducted using Publish or Perish to identify studies indexed in Scopus and Google Scholar. The review followed the PRISMA 2020 framework and included peer-reviewed publications as well as relevant grey literature (e.g., theses, classroom-developed projects), acknowledging that many pedagogical innovations in music education are not always disseminated through formal journals. The initial search resulted in 124 records; after screening for eligibility and methodological clarity, 26 studies were included in the synthesis. Most studies emphasized ear-training and quiz-based game formats, while rhythm-based, exploratory, and curriculum-integrated designs appeared less frequently. Research contexts were dominated by beginner learners, elementary education, and university courses, with only a small number of studies focusing on senior high school contexts. These findings highlight gaps in current research and indicate the need for future game designs that support sustained perceptual training and integrate culturally grounded approaches to music learning.